Multiproxy analyses of the Triassic Agua de la Zorra Formation, Cuyana Basin, Argentina: Palynofacies, geochemistry, and biotic record. (October 2021) - Pedernera, Tomás E.; Ottone, Eduardo G.; Mancuso, Adriana C.; Erra, Georgina; Larriestra, Fernando; Benavente, Cecilia A.; Pineda Alvarez, Juan Agustin; Campos, Claudio; Bustos Escalona, Evelyn Luz; Krapovickas, Veronica; Marsicano, Claudia A.
Abstract: The Triassic Agua de la Zorra Formation crops out in the Paramillos de Uspallata area (NW of Mendoza) and represents a deltaic-lacustrine system with volcanic activity as well as episodic incursions of peperitic basalts. The succession is characterized by distal lacustrine facies at base and top, with proximal shallow facies in the middle section. The paleontological record includes invertebrates (spinicaudatans, insects), vertebrates (mainly fishs), tetrapod tracks and invertebrates traces, and plant remains (mainly referred to Umkomasiales). Kerogen in the distal facies is mostly terrigenous, with scarce amorphous and palynomorphs (disacates and microalgae). It shows a variable percentage of the total organic carbon content (between 0.2 and 4.6) with hydrogen and oxygen indices indicating a type III kerogen. In the shallow facies, kerogen is practically absent and the trace fossils reflect sporadic subaerial exposure. The palynological evidence indicates an oligotrophic lake and the low productivity recorded was likely caused by dilution of the lake water by strong fluvial influence in an overfilled lake basin type. The organic geochemistry data also suggests an overfilled lake basin and the inorganic geochemistry data support the development of anoxic conditions at the bottom of the paleolake. The spinicaudata valves occur in densely packed beds that could have been driven by changes in the water physicochemical parameters as a result of volcanic activity in the area. The volcanic activity in the area is a good explanation for variability in the biota diversity. However, the continuous record of plant remains through out the section seems to indicates that the paleoenvironmental conditions in the surrounding terrestrial areas were stables. Highlights: The palynological evidence indicates a lake with low productivity. The organic geochemistry data is consistent with the parameters of an overfilled lake basin. The spinicaudata beds registered could be driven by changes in the physicochemical parameters caused by volcanic activity. The trace fossils recorded seem to reflect a sporadic subaerial exposure of the sediments. The volcanic activity in the area is a good explanation for variability in the biota diversity.